The effect of silk gland sericin protein incorporation into electrospun polycaprolactone nanofibers on in vitro and in vivo characteristics. Issue 5 (5th December 2014) - Li, Linhao; Qian, Yuna; Lin, Chongwen; Li, Haibin; Jiang, Chao; Lv, Yonggang; Liu, Wanqian; Cai, Kaiyong; Germershaus, Oliver; Yang, Li
Abstract : Silk middle gland extracted sericin protein based electrospun nanofibrous scaffolds with excellent biocompatibility have been developed for tissue engineering applications. Abstract : The application of silk fibroin is a promising approach for designing biomaterials. However, silk sericin (SS) protein has not attracted much attention in the field of biomaterials as a natural biopolymer due to its immune responses, weak structural properties and high solubility. In this study, fifth instar silkworm ( B. mori ) middle gland extracted sericin protein and polycaprolactone (PCL) blends nanofibrous scaffolds were successfully fabricated via an emulsion electrospinning technique. PCL/SS nanofibrous scaffolds were characterized by combined techniques of scanning electron microscopy (SEM), transmission electron microscopy (TEM), and Fourier transform infrared spectroscopy (FTIR). Water contact angle and tensile measurements indicated that the PCL/SS scaffolds exhibited improved mechanical properties, as well as more favorable wettability, than that obtained from PCL alone. We also analyzed the effect of SS content in blends on cell morphology and proliferation of human primary skin fibroblasts (FEK4 cells) within 1–5 days. The results showed that cell proliferation significantly increased in the appropriate ratio of PCL/SS blends while showing more elongated cellular morphology. The mRNA gene expression of transforming growth factor β1 (TGF-β1) and collagen I were up-regulated in PCL/SS scaffolds. Furthermore, in vivo experiments suggested that low fibrosis tissue formation and macrophages adhesion of the PCL/SS nanofibrous scaffolds reveal its potential as future biocompatible scaffolds for tissue engineering.